Customer satisfaction towards fast food restaurant: a focus on RASAMAS Restaurant / Anin Zabidah Idris - Idris, Anin Zabidah (Faculty of Business and Management, 2010)
A study was conducted to know the level of customer satisfactions towards RasaMas Restaurant. The main objectives of this study were to identify attributes that influence customer satisfactions and determine their relationships with customer satisfactions. The variables included in this research are food quality, service quality and servicescape/ambience as independent variables and customer satisfactions as the dependent variable. A survey questionnaire which consisted of three parts to measure demographic factors, independent variables and dependent variables was constructed based on items determined by past research. 200 respondents at Klang valley area were selected as a sample. Cronbach Alpha testing was conducted to determine the reliability and validity of questionnaire. The result of Reliability analysis indicates that all questions are reliable because Cronbach’s Alpha of all variables is 0.932 which is at the range of excellent. Therefore, overall of variables could be accepted for this study. From the findings, there were positive significant relationship between food quality (r=0.682**, p=0.000), service quality (r=0.618**, p=0.000) and servicescape/ambience (r=0.731**, p=0.000) with customer satisfactions. Besides, the results show that servicescape/ambience is the most factors that influence customer satisfactions which its Beta value is 0.453. For future researchers could concentrate on the reasons for servicescape/ambience is currently becoming the leading factor in determining customer satisfactions. Some conclusions are provided in the research and the researcher also has stated several recommendations which are essential to RasaMas Restaurant to increase customer satisfaction towards them.